2010
DOI: 10.1111/j.1476-5381.2010.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing effects of exogenous and endogenous hydrogen sulphide in carrageenan‐induced knee joint synovitis in the rat

Abstract: Background and purpose: Recent findings suggest that the noxious gas H2S is produced endogenously, and that physiological concentrations of H2S are able to modulate pain and inflammation in rodents. This study was undertaken to evaluate the ability of endogenous and exogenous H2S to modulate carrageenan-induced synovitis in the rat knee. Experimental approach: Synovitis was induced in Wistar rats by intra-articular injection of carrageenan into the knee joint. Sixty minutes prior to carrageenan injection, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 52 publications
1
70
0
9
Order By: Relevance
“…In agreement with our data, Zanardo and co-workers [48] have shown that spontaneous H2S donors, such as Na2S, NaHS and LR, markedly inhibited carrageenan-induced leukocyte adhesion and infiltration in a rodent air pouch model. Similar results were obtained by Ekundi-Valentim and co-workers [16,20] in the model of carrageenan-induced synovitis in rats, and by Fiorucci and coworkers [49] in the acetyl salycilic acid-induced gastric injury in rats. Reduced expression of the adhesion molecules ICAM-1, VCAM-1, LFA-1, P-selectin, E-selectin in both endothelium and leukocytes has been suggested as the underlying mechanism of H2S-mediated inhibition of leukocyte influx [40,[48][49][50].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In agreement with our data, Zanardo and co-workers [48] have shown that spontaneous H2S donors, such as Na2S, NaHS and LR, markedly inhibited carrageenan-induced leukocyte adhesion and infiltration in a rodent air pouch model. Similar results were obtained by Ekundi-Valentim and co-workers [16,20] in the model of carrageenan-induced synovitis in rats, and by Fiorucci and coworkers [49] in the acetyl salycilic acid-induced gastric injury in rats. Reduced expression of the adhesion molecules ICAM-1, VCAM-1, LFA-1, P-selectin, E-selectin in both endothelium and leukocytes has been suggested as the underlying mechanism of H2S-mediated inhibition of leukocyte influx [40,[48][49][50].…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, over the last ten years, hydrogen sulfide (H2S) a new mediator that belongs to the class of endogenous gases such as nitric oxide (NO) and carbon monoxide (CO), has emerged and brought about divergent findings regarding its role in acute / chronic inflammatory responses and nociception [16][17][18][19]. However, the use of slow-releasing H2S donors (such as SG-1002, diallyl trisulfide and GYY4137) and hybrid H2S-releasing non steroidal anti-inflammatory compounds (such as the naproxen derivative strengthens the beneficial therapeutical effects of H2S in articular inflammation [20], colorectal cancer [21], periodontitis [22] and pain [23] with additional gastrointestinal safety [24].…”
Section: Introductionmentioning
confidence: 99%
“…This method was refined by adapting the assay for modern spectrophotometry [18] and more recently has been used for detection of sulfides in biological samples [20][21][22][23]. However there has been much debate if the current direct method is accurate and sensitive enough to measure free sulfides in tissue and plasma [13,14,27].…”
Section: Discussionmentioning
confidence: 99%
“…The method is based on the modified version [18] of the originally published method by Fischer et al [19] used to determine sulfide concentration in water and other nonbiological samples, but has been recently been adapted to determine sulfide content and synthesis in biological samples [20][21][22][23]; however there are limitations in doing so. The acidic nature of the assay could potentially liberate bound acid labile sulfur [13,14], thus causing artefacts, while coloured substances could interfere with the assay [24].…”
Section: Introductionmentioning
confidence: 99%
“…Tem efeito pró-nociceptivo quando administrado por via intratecal (Maeda et al, 2009), intraplantar (Kawabata et al, 2007 ou intracolônica Por outro lado, as propriedades anti-inflamatórias do H 2 S têm sido observadas em diversos modelos experimentais, tais como o de edema de pata induzido por CGN (Zanardo et al, 2006), artrite (Ekundi-Valentim et al, 2010;Li et al, 2013), lesão pulmonar (Esechie et al, 2008), asma (Benetti et al, 2013) e em modelo de dor viceral induzida por distensão coloretal (Distrutti et al, 2010).…”
Section: Sulfeto De Hidrogênio Na Inflamação E Nocicepçãounclassified